Community conflict, tension and life in new environment: Conflict and its impact on Vadda community in Mahaweli resettlement schemes in Sri Lanka - Epa, Pulsie; Wang Yi Jie; Hu Liang (Dynamics of Rural Society Journal, 2025)
There is a strong relationship between conflict and resettlement, as displaced communities often undergo resettlement following violent conflicts. It is important to consider conflicts during and after the resettlement process and their impact on the community. This study aimed to investigate community disputes in resettlement areas and their impact on daily activities. The qualitative research used an inductive and exploratory approach, applying reflexive thematic analysis. Eighteen respondents were selected through purposive sampling for semi-structured interviews from a resettlement scheme in Hennanigala South, Mahaweli "C" Zone, Sri Lanka. Various types of conflicts were identified, including human-wildlife, community-government officials, identity, community, and resource conflicts. These conflicts are driven by factors such as population growth, agricultural modernization, illegal encroachment, and environmental imbalance. They have led to social, economic, cultural, and psychological impacts on the community. Addressing these conflicts requires establishing a conflict mitigation and resolution system at policy and practical levels. Effective resolution involves careful planning, community engagement, and policy enforcement to protect the rights and welfare of the resettled population. Resolving conflicts necessitates effective communication, empathy, and willingness to compromise.